The influence of individual characteristics and leadership styles on the commitment and performance of State Civil Apparatus - Nurbaya Nurbaya; Aryana Satrya; Mestika Sekarwinahyu (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research is concerned with the effect of individual characteristics and leadership style towards the commitment and performance of Civil Servants in the regional apparatus organizations under the coordination of government assistants and the welfare of the Regional Secretary of Sumbawa Regency. The respondents of this study were 216 Civil Servants in regional apparatus organizations under the coordination of the Assistant Government and People's Welfare Regional Secretariat of Sumbawa Regency. This research is quantitative research design. To collect the data of this study, the researcher used questionnaires that conducted by online method and processed and analyzed by used Structural Equation Modeling (SEM) by the help of Jamovi software. The results showed that the individual characteristics have a positive and significant effect on the Civil Service Employee’s performance. However, the individual characteristics have a positive and significant effect towards their commitment. The leadership style does not have a positive and significant effect on the civil servants’ performance but, the leadership style has a positive and significant effect on their commitment, also the organizational commitment has a positive and significant effect towards the performance the Civil Servants in regional apparatus organizations under the coordination of the Assistant Government and People's Welfare Regional Secretariat of Sumbawa Regency.